Sleep disturbances in Rett syndrome: Impact and management including use of sleep hygiene practices - Boban, S.; Leonard, H.; Wong, K.; Wilson, A.; Downs, Jennepher (John Wiley & Sons, Inc., 2018)
© 2018 Wiley Periodicals, Inc. Sleep disturbances are debilitating for individuals with Rett syndrome (RTT) and their families yet the evidence base for management is poor. We investigated management strategies and their relationships with sleep problems. Data were provided by 364/461 (79%) families with a child with RTT and registered with the International RTT Phenotype Database. Logistic regression models were used to investigate relationships between impacts of sleep problems on the child and family with age group, mutation type, medication type, and sleep hygiene score. Linear regression models were used to estimate the association of disorders of initiating and maintaining sleep (DIMS) with age group, mutation type, medication type, and sleep hygiene. Among those who ever had difficulty falling asleep or night waking, use of any medication was associated with higher odds of moderate/major impact sleep problems (relative to minor/no impact) for the affected child and the family, as well as higher DIMS scores, when compared with the no treatment/nonmedication group accounting for the effects of age, mutation type, and sleep hygiene score. Better use of sleep hygiene practices was associated with lower odds of moderate/major impact on the family (odds ratio 0.60, 95% confidence intervals [CIs] 0.37, 0.98) and lower DIMS scores (geometric mean ratio 0.86, 95%CI 0.80, 0.92) compared with poorer use after adjusting for covariates. Attention to sleep hygiene remains an important management strategy for sleep problems in RTT. Further prospective research is required to investigate efficacy of pharmaceutical treatments.